Rice Prices and the National Food Authority - Ponciano Jr. S. Intal; Leah Francine Cu; Jo Anne Illescas (Philippine Institute for Development Studies (PIDS), 2012)
This study examines the performance of the National Food Authority (NFA) with respect to its function of price stability and implications for public finances, and recommends policy reforms where warranted. It finds that NFA has been unsuccessful in stabilizing producer prices, but relatively successful in stabilizing retail prices, largely through exercise of its import monopoly. However, it does so at high cost, partly due to operational inefficiency, but largely owing to its fundamental policy mandate. The study recommends relinquishing this mandate, and leaving a greater role for the private sector in stabilizing rice prices, with NFA function and price policy limited to maintaining strategic reserves a variable import levy.
Keywords: 330; Philippines; price stabilization; food security; National Food Authority (NFA); financial sustainability